Boulder deposits on the southeastern coast of Cyprus and their relation with palaeotsunami events of the Eastern Mediterranean - Evelpidou, N.; Synolakis, C.; Zerefos, C.; Repapis, C; Karkani, A.; Polidorou, M.; Saitis, G. (RCG2019 “Geomorphology of Climatically and Tectonically Sensitive Areas”, 2019)
Cyprus has a long record of tsunami waves, as noted by archaeological and geological records. Large boulder deposits have been noted in southeastern and western part of the Island. In the area of Cape Greco (southeastern Cyprus) large boulders have been noted, however, no detailed geomorphological research exists so far and the related high energy event remains undated. In this context, we focused at Cape Greco Peninsula at the southeastern coast of Cyprus, in order to record in detail large boulders deposits. The accumulation of the boulders along the uplifted coastline (3m amsl) was recorded. The boulders are fragments of a layer of an upper Pleistocene aeolianite, which is overlaying unconformly a lower Pleistocene calcarenite. Dimensions and spatial distribution of 272 small, medium and large boulders were documented. The precise distance of the boulders deposition from the coastline was recorded by field measurements and remote sensing with the use of GNSS, Drone mapping and GIS technics. Several large boulders weighting more than ~30 metric tons were located up to 60m inland. Geomorphologic mapping and morphometric measurements, along with the presence of marine organisms suggests that some of the boulders were removed from their original intertidal zone and were transported inland by the force of large waves. Samples of Vermetus sp. were collected from the displaced boulders in order to date the extreme event. In this work, we report and compare preliminary results from the application of widely accepted hydrodynamic equations, in order to determine the extreme event that caused their transport inland. We further attempt a correlation of the event with already known tsunami events from Eastern Mediterranean, based on the estimated wave heights and the radiocarbon dating of marine gastropods (Vermetus sp.).